REINTERPRETATION OF MASS NGABEN IN BALI - Ni Wayan Suastini (E-Journal of Cultural Studies, 2020)
The essence of the implementation of the “Ngaben Massal” ceremony, is a deconstruction of hegemonic discourse in society, a deconstruction of the hegemonic tradition in the Ngaben discourse, starting from the rise of philosophical public awareness starting from the clearer understanding of society in religious literature. From this understanding, other reinterpretations emerge, such as reinterpretation of the meaning of economy, social solidarity and education. This reinterpretation of the meaning of the Ngaben ceremony is a very important basis for appreciation so that mass Ngaben can be widely accepted in most community groups. The implementation of the above is very important that can be grown in the implementation of the Mass Ngaben Ceremony, as a medium of education, is the emergence of public awareness of the essential values ??of a yajna ceremony such as the Ngaben Ceremony itself. So that the essential value of a yajña ceremony (Ngaben) is no longer buried by the routine of a tradition, which is nothing more than a traditional obligation which can give the impression that a yajñas ceremony like Ngaben with the hegemonic tradition is just a burden of tradition that is independent of its essence and meaning. Keywords: Mass Ngaben, deconstruction, discourse, cultural hegomony